Students’ Attitude and Learning Satisfaction Towards Science and Its Effects on Academic Performance - Tanghal, Analiza B (ASEAN Journal of Basic and Higher Education, 2020)
This study envisioned to explore students’ attitude toward Science as a subject and their learning satisfaction. The respondents of the study were 150 senior high school students of the San Josef National High School, Purok 1, San Josef Sur, Cabanatuan City, Nueva Ecija during the academic year 2018-2019. Both grades 11 and 12 students were considered taking into account their exposure to more varied academic activities in their subject in Science. Focus of the study were on two constructs: students’ attitude toward Science and three measures of learning contentment: motivation, impressions towards formidable tasks, and comprehensibility of lessons. Socio-demographic of the learners were the profile variables for correlation. Academic learning performance was based on the grades obtained by the students in Science during the preceding school year. The Descriptive method of research was used in this study. The researcher used checklist and survey questionnaires as mean of gathering data. The data were treated by all of the formulas embedded in the trial version of SPSS (Statistical Package for Social Sciences). Students’ attitude toward Science was found to be significantly related to the three aspects of learning satisfaction. Also, students’ attitude towards Science and the three aspects of learning satisfaction had significant relationship to students’ academic learning performance in Science. Since learners already had high learning gratification in terms of motivation, comprehensibility, and impressions towards formidable tasks, teachers of Science may incessantly monitor students’ satisfaction and gratification in their quest for knowledge and in their desire to come up with competencies relative to Science.